C-Type Lectin-Like Receptors As Emerging Orchestrators of Sterile Inflammation Represent Potential Therapeutic Targets - Chiffoleau, Elise (Frontiers in Immunology, 2018)
Over the last decade, C-type lectin-like receptors (CTLRs), expressed mostly by myeloid cells, have gained increasing attention for their role in the fine-tuning of both innate and adaptive immunity. Not only, CTLRs recognize pathogen-derived ligands to protect against infection, but also endogenous ligands such as self-carbohydrates, proteins or lipids to control homeostasis and tissue injury. Interestingly, CTLRs act as antigen-uptake receptors via their carbohydrate recognition domain for internalization and subsequent presentation to T-cells. Furthermore, CTLRs signal through a complex intracellular network leading to the secretion of a particular set of cytokines that differently polarizes downstream effector T-cell responses according to the ligand and pattern recognition receptor co-engagement. Thus, by orchestrating the balance between inflammatory and resolution pathways, CTLRs are now considered as driving players of sterile inflammation whose dysregulation leads to the development of various pathologies such as auto-immune diseases, allergy or cancer. For examples, the macrophage-inducible C-type lectin (MINCLE), by sensing glycolipids released during cell-damage, promotes skin allergy and the pathogenesis of experimental autoimmune uveoretinitis. Besides, recent studies described that tumors use physiological process of the CTLRs dendritic cells-associated C-type lectin-1 DECTIN-1 and MINCLE to locally suppress myeloid cell activation and promote immune evasion. Therefore, we aim here to overview the current knowledge of the pivotal role of CTLRs in sterile inflammation with special attention given to the “Dectin-1” and “Dectin-2” families. Moreover, we will discuss the potential of these receptors as promising therapeutic targets to treat a wide range of acute and chronic diseases.